The Constitutional Court as a Positive Legislative through the Living Constitution Approach - Lina Sinaulan, Ramlani; Saputra, Rahmat; Sugeng Sugeng (International Journal of Law and Society, 2025)
This study examines the role of the Constitutional Court of Indonesia (Mahkamah Konstitusi/MK) as a positive legislator through the lens of the living constitution approach, which conceptualizes the constitution as a dynamic and evolving document responding to social and political change. The main problem addressed is the extent to which the MK’s judicial activism in interpreting and even creating new legal norms aligns with constitutional principles, democratic legitimacy, and the balance of powers between the judiciary and the legislature. The objective of the research is to analyze how the MK’s progressive interpretations have transformed it from a negative legislator—which merely annuls unconstitutional laws—into a positive legislator that effectively fills legal gaps and constructs new constitutional meanings. Using a normative juridical method combined with case study analysis, this research explores key constitutional decisions, focusing on cases where the MK extended its interpretive authority beyond mere judicial review. The findings reveal that the MK, through the living constitution approach, justifies its role as a positive legislator by invoking principles of constitutional morality, justice, and responsiveness to societal evolution. However, this judicial creativity also generates tension with legislative supremacy and may risk overstepping the boundaries of judicial function. The synthesis of findings suggests that the MK’s transformation embodies the dynamic interplay between constitutional text and social context, reinforcing the adaptability of Indonesian constitutionalism. The study concludes that while the MK’s position as a positive legislator under the living constitution paradigm strengthens constitutional justice and protects citizens’ rights, it must remain anchored in checks and balances to prevent judicial overreach and preserve democratic legitimacy.